Phenological behaviour and heat unit requirement of groundnut (Arachis hypogaea) genotypes under two dates of sowing during summer season - BRAR, AJMER SINGH; DHINGRA, K K; KAUL, J N (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during summer season of 1995 and 1996 to study the phenology and heat unitrequirement of the groundnut (Arachis hypogaea L.) genotypes as influenced by 2 dates of sowing. The 2 groundnut.genotypes, viz 'M 13' and 'M 335' being of longer duration accumulated higher growing degree days, helio-thennalunit and photo-thermal units at all the phenophases than the 'M 522', 'SO 84' and local genotypes. 'SO 84' the shortduration bunch genotype attained harvest maturity 5-10 days earlier than the other 4 genotypes and translocated highestdry-matter towards pods at 93 and 114 days, while total dry-matter/plant was maximum in 'M 522' during both theyears. The date of sowing did not influence the various phenophases of any genotype.